Informed consent: Montgomery trumps Bolam. Issue 3 (May 2017) - Mansell, Josephine; Mansell, Martin
Abstract : The old paternalistic system, where doctors could decide what to tell patients about the risks involved in a procedure, has gone. In this article, the authors describe how the requirements around informed consent are now clearly defined and need to be heeded.